The impact of the ionosphere on ground-based detection of the global Epoch of Reionisation signal - Sokolowski, M.; Wayth, Randall; Tremblay, S.; Tingay, Steven; Waterson, M.; Tickner, J.; Emrich, D.; Schlagenhaufer, F.; Kenney, D.; Padhi, S. (2015)
The redshifted 21cm line of neutral hydrogen (Hi), potentially observable at low radio frequencies (~50-200 MHz), is a promising probe of the physical conditions of the inter-galactic medium during Cosmic Dawn and the Epoch of Reionisation (EoR). The sky-averaged Hi signal is expected to be extremely weak (~100 mK) in comparison to the Galactic foreground emission (~10 4 K). Moreover, the sky-averaged spectra measured by ground-based instruments are affected by chromatic propagation effects (of the order of tens of Kelvins) originating in the ionosphere. We analyze data collected with the upgraded BIGHORNS system deployed at the Murchison Radio-astronomy Observatory to assess the significance of ionospheric effects (absorption, emission and refraction) on the detection of the global EoR signal. We measure some properties of the ionosphere, such as the electron temperature (T e ≈ 470 K at nighttime), magnitude, and variability of optical depth (τ 100MHz ≈ 0.01 and δτ≈ 0.005 at nighttime). According to the results of a statistical test applied on a large data sample, very long integrations lead to increased signal to noise even in the presence of ionospheric variability. This is further supported by the structure of the power spectrum of the sky temperature fluctuations, which has flicker noise characteristics at frequencies ≥10 −5 Hz, but becomes flat below ≈10 −5 Hz. We conclude that the stochastic error introduced by the chromatic ionospheric effects tends to zero in an average. Therefore, the ionospheric effects and fluctuations are not fundamental impediments preventing ground-based instruments from integrating down to the precision required by global EoR experiments.